The efficacy of anti-TNF in rheumatoid arthritis, a comparison between randomised controlled trials and clinical practice. Issue 11 (10th April 2007) - Kievit, W; Fransen, J; Oerlemans, A J M; Kuper, H H; van der Laar, M A F J; de Rooij, D J R A M; De Gendt, C M A; Ronday, K H; Jansen, T L; van Oijen, P C M; Brus, H L M; Adang, E M; et al.
Abstract : Background: Randomised controlled trials (RCTs) evaluating the efficacy of antagonists to tumour necrosis factor α (TNFα) showed high response percentages in the groups treated with active drugs. Objective: To compare the efficacy of anti-TNF treatments for rheumatoid arthritis (RA) patients in RCTs and in daily clinical practice, with an emphasis on the efficacy for patients eligible and not eligible for RCTs of anti-TNF treatments. Methods: First, randomised placebo-controlled trials written in English for etanercept, infliximab and adalimumab for patients with RA were selected by a systematic review. Second, the DREAM (Dutch Rheumatoid Arthritis Monitoring) register with patients starting for the first time on one of the TNF-blocking agents was used. Patient characteristics, doses of medication and co-medication as well as the ACR20 response percentages were compared between RCTs and DREAM data, stratified for trial eligibility. Results: In 10 of 11 comparisons, the ACR20 response percentages were lower in daily clinical practice than in the RCT active drug group, which was significant in five of 11 comparisons. Only 34–79% of DREAM patients fulfilled the selection criteria for disease activity in the several RCTs examined. DREAM patients eligible for RCTs had higher response percentages than ineligible DREAM patients. ACR20 response percentages of eligible DREAM patients were comparable with the ACR20 response percentages of the RCT active drug group in 10 of 11 comparisons. Conclusion: The efficacy of TNF-blocking agents in RCTs exceeded the efficacy of these drugs in clinical practice. However, in clinical practice more patients with lower disease activity were treated with TNF-blocking agents compared with those treated in RCTs. For daily practice patients who were eligible for RCTs, responses were more similar to responses reached in RCTs.